Menstrual Cycle in Trauma-Related Disorders: A Mini-Review - Mu, Eveline; Thomas, Elizabeth H. X.; Kulkarni, Jayashri (Frontiers in Global Women's Health, 2022)
Fluctuations of sex hormones across the menstrual cycle have been linked to exacerbation of symptoms of psychiatric disorders. Women diagnosed with trauma-related disorders such as post-traumatic stress disorder (PTSD) and borderline personality disorder (BPD) have reported worsening of mood symptoms at various phases of their menstrual cycle. There is also considerable overlap between PTSD, BPD, and complex-PTSD (cPTSD) symptoms, suggesting similar biological underpinnings. This mini-review examines the influence of sex hormones and the menstrual cycle on PTSD, BPD, and cPTSD symptoms, and discusses the involvement of the hypothalamic-pituitary-adrenal (HPA) axis. We review literature showing that PTSD and BPD symptoms fluctuate with the menstrual cycle, though the effect of the menstrual cycle phase appears to be inconsistent, warranting future research. Based on the reported phasic vulnerability in individuals with PTSD and BPD, it is plausible to assume that women diagnosed with the newly introduced cPTSD may experience similar difficulties. However, no study to date has addressed this. This review highlights the importance of considering an individual's trauma history as it may influence symptom severity and diagnosis, and the phase of the menstrual cycle at the time of diagnosis. This review also highlights that additional work is needed to clarify the influence of estradiol and progesterone fluctuations on trauma-related symptoms, especially in cPTSD. Continued research on menstrual cycle vulnerability and trauma will lead to better informed management and treatment of PTSD, BPD, and cPTSD. Keywords: PTSD, BPD, cPTSD, trauma, estradiol, progesterone